Analisis Faktor-Faktor Internal yang Mempengaruhi Pendapatan Restorant Citranoodle+ - Benaya Dustin; Carolyn Natalia; Alvin Alexis; Genesis Charitos; Dyah Cahyasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The business landscape in Tangernag Regency has experienced significant growth compared to before due to the Covid-19 pandemic. The development of business opportunities in an area can increase the income and economy of that area. The accommodation and food and beverage provider business sector is one of the sectors that contributes to economic growth in Tangerang Regency, especially in the Gading Serpong, BSD and surrounding areas. Citra Noodle+ is a business that sells noodles in the Gading Serpong area. The aim of the research is to look for factors that can influence CitraNoodle+’s income. Primary data wa obtained using interview and observation methods, with secondary data obtained through a literature review.